Epigenome-wide analysis of methylation changes in the sequence of gallstone disease, dysplasia, and gallbladder cancer - Brägelmann, Johannes; Barahona Ponce, Carol; Marcelain, Katherine; Rössler, Stephanie; Goeppert, Benjamin; Gallegos, Ivan; Colombo, Alicia; Sanhueza, Verónica; Morales, Erik; Rivera, María Teresa; de Toro, Gonzalo; Ortega, Alejandro; et al. (Hepatology, 2021)
Background and Aims Gallbladder cancer (GBC) is a highly aggressive malignancy of the biliary tract. Most cases of GBC are diagnosed in low-income and middle-income countries, and research into this disease has long been limited. In this study we therefore investigate the epigenetic changes along the model of GBC carcinogenesis represented by the sequence gallstone disease → dysplasia → GBC in Chile, the country with the highest incidence of GBC worldwide. Approach and Results To perform epigenome-wide methylation profiling, genomic DNA extracted from sections of formalin-fixed, paraffin-embedded gallbladder tissue was analyzed using Illumina Infinium MethylationEPIC BeadChips. Preprocessed, quality-controlled data from 82 samples (gallstones n = 32, low-grade dysplasia n = 13, high-grade dysplasia n = 9, GBC n = 28) were available to identify differentially methylated markers, regions, and pathways as well as changes in copy number variations (CNVs). The number and magnitude of epigenetic changes increased with disease development and predominantly involved the hypermethylation of cytosine-guanine dinucleotide islands and gene promoter regions. The methylation of genes implicated in Wnt signaling, Hedgehog signaling, and tumor suppression increased with tumor grade. CNVs also increased with GBC development and affected cyclin-dependent kinase inhibitor 2A, MDM2 proto-oncogene, tumor protein P53, and cyclin D1 genes. Gains in the targetable Erb-B2 receptor tyrosine kinase 2 gene were detected in 14% of GBC samples. Conclusions Our results indicate that GBC carcinogenesis comprises three main methylation stages: early (gallstone disease and low-grade dysplasia), intermediate (high-grade dysplasia), and late (GBC). The identified gradual changes in methylation and CNVs may help to enhance our understanding of the mechanisms underlying this aggressive disease and eventually lead to improved treatment and early diagnosis of GBC.
First published: 05 October 2020
Gesehen am 06.12.2021